SISTEMA EXPERTO PARA LA PREVENCIÓN DE ENFERMEDADES BASADO EN EL CONSUMO DE ALIMENTOS COTIDIANOS - Vega H y Cols., Hugo (2019)
Throughout human existence, the treatment of illnesses has always been a constant concern. Now that the world population has increased and the illnesses have multiplied, the sale of drugs has become one of the main businesses in the world. Like we know, natural medicine is an important alternative in the treatment and prevention of illnesses. Given these assumptions, we have made an important investigation it has allowed us to generate this article. The objective of this article is to explain the how to model an Expert System for the prevention and treatment of illnesses based on the daily food consumption. In summary, the Expert System (ES) that we have modelling, permit you to register as entry symptoms, illnesses, or medical test results from a patient and generates as output a list of alternatives of foods that the patient should consume at breakfast, lunch, and supper. Thus, the patient relieves their symptoms, maintaining where possible their normal food consumption habits. Of course the ES will be responsible for the linkage of the dishes recommended by the system with natural products that relieve the symptoms registered as input. Obviously, for each patient with different symptoms, it is hoped that ES recommend different dishes.